The Three Cases of Mother-Daughter Relationship in Croatian Literature - Gjurgjan, Ljiljana Ina (1992)
This article takes both the question of canon and of voice one stage further, by addressing areas related to women's lives hitherto unexplored by male Croatian writers, thereby setting a new agenda for the canon and creating space for a new voice. the paper discusses three Croatian novels: Vjenceslav Novak's "The Last of the Stipančić's", Irena Vrkljan's "Silk Scissors" and Slavenka Drakulić's "The Marble Skin" - in order to examine how the canon and the voice change in exploring the mother-daughter relationship.
Rad je kao poster prezentiran na skupu Women's Vocie in Literature and Society, održanom 1992., Bradford, Engleska.
Projekt MZOS
Projekt MZOS
ENG